Clinical testing of pre-pandemic live attenuated A/H5N2 influenza candidate vaccine in adult volunteers: Results from a placebo-controlled, randomized double-blind phase I study. Issue 39 (22nd September 2015) - Rudenko, Larisa; Kiseleva, Irina; Stukova, Marina; Erofeeva, Marianna; Naykhin, Anatoly; Donina, Svetlana; Larionova, Natalie; Pisareva, Maria; Krivitskaya, Vera; Flores, Jorge; the Russian LAIV Trial Study Group, 1
Highlights We performed phase I clinical trial of A/H5N2 LAIV in healthy volunteers. The vaccine was safe and well tolerated. Vaccine virus was detected by PCR in nasal swabs in the majority of vaccinees. No viral RNA was detected in any of the placebo recipients after vaccination. Overall, an immune response was observed in over 96% subjects that received LAIV.